2011
DOI: 10.1177/1476127011415246
|View full text |Cite
|
Sign up to set email alerts
|

Post-acquisition structuring of CEO pay packages: Incentives and punishments

Abstract: Posited on the asymmetric features of equity ownership and stock option pay, this article examines the extent to which acquisition activities affect boards of directors' decisions to restructure the incentive design of executive compensation packages in the post-acquisition period. For a recent dataset of 148 deals between 1996 and 2009, the article finds that acquirers' overpayment for target firms and equity financing are likely to require scapegoating, particularly under conditions of intervening poor perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 132 publications
(280 reference statements)
0
23
0
Order By: Relevance
“…57,58 The relationship is essentially hierarchic where the practitioner, because ª 2012 Blackwell Publishing Ltd Health Expectations, 16, pp. [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] Governance mechanisms in the physician-patient relationship, G Tofan, V Bodolica and M Spraggon Governance mechanisms in the physician-patient relationship, G Tofan, V Bodolica and M Spraggon of expert knowledge and skills, possesses the authority to make decisions on patients' behalf with little consideration of their preferences. 59 Being constrained to assume a passive role and submit to physician's professional judgments, patients ought to invest their trust in the physician's fiduciary obligation of making patients' health a top priority.…”
Section: Trust-based Governancementioning
confidence: 99%
See 3 more Smart Citations
“…57,58 The relationship is essentially hierarchic where the practitioner, because ª 2012 Blackwell Publishing Ltd Health Expectations, 16, pp. [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] Governance mechanisms in the physician-patient relationship, G Tofan, V Bodolica and M Spraggon Governance mechanisms in the physician-patient relationship, G Tofan, V Bodolica and M Spraggon of expert knowledge and skills, possesses the authority to make decisions on patients' behalf with little consideration of their preferences. 59 Being constrained to assume a passive role and submit to physician's professional judgments, patients ought to invest their trust in the physician's fiduciary obligation of making patients' health a top priority.…”
Section: Trust-based Governancementioning
confidence: 99%
“…63 In a study of Australian patients, it was reported that the medical ª 2012 Blackwell Publishing Ltd Health Expectations, 16, pp. [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] Governance mechanisms in the physician-patient relationship, G Tofan, V Bodolica and M Spraggon literacy of consumers enhanced their trust in caregivers. 76 To regain patient trust, some scholars plead for a governance model of optional autonomy and collaboration between participants, 62 while others call for a renewed commitment to moral integrity and ethical decision making.…”
Section: Trust-based Governancementioning
confidence: 99%
See 2 more Smart Citations
“…These norms include formal mechanisms of control which are enforced by a regulatory body or institution holding legitimate power. In the absence of internalized moral values, the only indication that these managers have of what can be justified as morally correct is provided by the national system of laws and regulations (Spraggon & Bodolica ). They will seek to inscribe their actions within the regulatory framework of their country with the objective of escaping from the harmful implications originating from a law‐infringing behavior.…”
Section: Trust Authentic Pride and Moral Reasoningmentioning
confidence: 99%